Illicit Drug Addiction and Efficacy of Employees in the Hospitality Industry - Akintola, Abayomi I.; Ada, Julius A.; Angioha, Pius U.; Ibioro, Francis E.; Igwe-Okomiso, Jospeph B.; Bisong, Kenneth B.; Ogunsola, O. V. (ARRUS Journal of Social Sciences and Humanities, 2022)
The study examined illicit drug addiction and employees' efficacy in the hospitality industry in Calabar, Cross River State, Nigeria. The study specifically examined how illicit drug addiction such as alcohol addiction and marijuana addiction affect employees' efficacy in the hospitality industry in Calabar, Cross River State, Nigeria. The descriptive survey research design was adopted for the study. The multi-stage sampling technique was used in selecting a sample of 297 from a population of 1,298 employees of the hospitality industry in Calabar Cross River State, Nigeria. Data was collected using a structured questionnaire. Data analysis was done using Regression analysis. The result revealed a statistically significant correlation between marijuana addiction, alcohol addiction, and employees' efficacy in the hospitality industry in Calabar, Cross River State, Nigeria. Based on this finding, the study recommended that employers in the hospitality industry put punitive measures that will curb employees' illicit addiction to drugs